2013
DOI: 10.1093/comnet/cnt001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic network centrality summarizes learning in the human brain

Abstract: We study functional activity in the human brain using functional magnetic resonance imaging and recently developed tools from network science. The data arise from the performance of a simple behavioural motor learning task. Unsupervised clustering of subjects with respect to similarity of network activity measured over 3 days of practice produces significant evidence of 'learning', in the sense that subjects typically move between clusters (of subjects whose dynamics are similar) as time progresses.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 33 publications
2
68
0
Order By: Relevance
“…Our results suggest that the extent and anatomical specificity of interhemispheric coordination is time-dependent, highlighting the usefulness of dynamic network methods to explore brain function (41,42,65). As shown in Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our results suggest that the extent and anatomical specificity of interhemispheric coordination is time-dependent, highlighting the usefulness of dynamic network methods to explore brain function (41,42,65). As shown in Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Examination of MEG data using these techniques has demonstrated that functional brain network organization is a biologically meaningful phenotype being altered in disease states (25) in ways that can be linked to behavioral task performance (60)(61)(62). Moreover, network organization demonstrates temporal variability that can be induced by cognitive remediation strategies (63), task practice (64), learning (41,53,65), or task difficulty (66).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, temporal stationarity assumptions are often violated in real-world applications. It is therefore of critical importance to divide the observed time series data into stationary segments [77], allowing for the inference of causal networks that are time-dependent [45]. Finally, information causality suggests physical causality, but they are not necessarily equivalent [33,53].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts in nonlinear dynamics define basins of attraction and perturbations driving a system between basins [14, 15]. Efforts in network science define graph metrics and report statistical correlations with observed functions such as attention [16] and learning [17, 18]. Neither approach offers comprehensive analytical solutions explaining mechanisms of control.…”
mentioning
confidence: 99%